2014
DOI: 10.3233/jad-140660
|View full text |Cite
|
Sign up to set email alerts
|

Non-Pharmacological Interventions for Patients with Mild Cognitive Impairment: A Meta-Analysis of Randomized Controlled Trials of Cognition-Based and Exercise Interventions

Abstract: Both of cognition-based intervention and physical exercise had the potential to improve global cognitive function. Weak evidence of improvements was also observed for the domains of executive function and delayed memory following cognition-based intervention. Nevertheless, future standard RCTs are still needed to identify the clinical value of our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 33 publications
5
64
0
4
Order By: Relevance
“…109 Another meta-analysis involving 14 randomized controlled trials (RCTs) found exercise had a very small significant effect on improving verbal fluency and no other significant effects. 110 Wang et al 111 found an effect of exercise on global cognitive function. Many of these studies were conducted over relatively short periods.…”
Section: Potential Benefits Of Early Diagnosis Of Cognitive Impairmentmentioning
confidence: 99%
“…109 Another meta-analysis involving 14 randomized controlled trials (RCTs) found exercise had a very small significant effect on improving verbal fluency and no other significant effects. 110 Wang et al 111 found an effect of exercise on global cognitive function. Many of these studies were conducted over relatively short periods.…”
Section: Potential Benefits Of Early Diagnosis Of Cognitive Impairmentmentioning
confidence: 99%
“…Although follow-up evaluations are important because aMCI is a degenerative condition in many individuals, they have not been conducted in many studies [8]. Further, most of the studies had a small sample size [8,9,10]. There is a lack of randomized placebo-controlled trials and standardization of training programs, with great variability in study design [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Further, most of the studies had a small sample size [8,9,10]. There is a lack of randomized placebo-controlled trials and standardization of training programs, with great variability in study design [8,9]. The efficacy of cognitive intervention in MCI remains to be verified in quality trials in large samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[100]. In a recent meta-analysis, cognition-based intervention was associated with improved global cognitive function in people with MCI and weak evidence of improvements in the specific domains of executive function and delayed memory [101]. However, these types of intervention rely on the resources to implement and sustain them in practice, and the field has a need to develop evidence-based training which can be sustained by the individuals.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%